Songs of Despair in Times of Contempt. On the Poetic Cycle of Márciustól Márciusig by István Vas - Piotrowiak-Junkiert, Kinga (Poznańskie Studia Slawistyczne, 2019)
The article offers an interpretation of the poetic cycle Od marca do marca [From March to March] by István Vas, a Hungarian poet and writer of Jewish origin. The author treated each of his poems as a notebook, where he recorded his reflections on the situation of Hungarian Jews, the human condition, the siege of Budapest, etc. For Vas, each piece is a separate testimony to the time of the war. The entire cycle is steeped in irony and a harsh judgement of the society’s moral fall. Vas wrote his poems during the period of Nazism but published them during the communist regime, when he wanted to answer a question about the role of art in the process of recovering historical memory, and whether a literary text could offer protection from the hostile reality.